(untitled) (Faridpur Medical College Journal, 2025)
Premature Rupture of Membranes is one of the important causes of preterm delivery and is associated with increased rates of neonatal and maternal morbidity and mortality. Maternal ascending infection is an important cause of Premature Rupture of membrane and may lead to life threatening sepsis in both mother and baby. This study was aimed to determine the antibiotic sensitivity pattern of microorganisms isolated from vagina of patient with premature rupture of membrane. It was a cross sectional study carried out in FMCH from August 2022 to January 2023 among pregnant women who met inclusion criteria. High vaginal swabs were collected by sterile speculum examination. Smears were sent to ICDDRB for culture and investigation of sensitivity patterns. Of the high vaginal swabs collected 28% were sterile and 72% had positive culture. The most common organism isolated was Staphylococcus aureus (42%) and second most commom E.coli (14%) other microbes isolated were Enterococcus (8%), Group B streptococcus (2%) and Bacteroides was (2%). Amoxiclav, Clindamycin, Gentamycin, Linezolid, Teicoplanin, Tigecycline, Vancomycin, Imipenem were found to have appropriate pattern. Common isolates were found to be resistant to Ampicillin, Erythromycin, Ceftriaxone. Use of appropriate antibiotic in Premature Rupture of Membrane can improve maternal and fetal outcome. Faridpur Med. Coll. J. 2025;20(1):19-23